(untitled) (GESTIÓN Y TENDENCIAS, 2021)
The right to repair (RTR) is a set of processes that allow consumers to extend the lifespan and functionality of their products through upgrade, maintenance, and corrective activities. In theory, RTR opposes throwaway culture and extends the life cycle of products, improves their safety, and contributes to a more sustainable environment. Several jurisdictions around the world have begun to implement rules guaranteeing RTR to their consumers. Most discussions center on consumer rights and do not consider the producer’s perspective. This article explores some of the implications of RTR from the producer’s point of view and its impact on product design and intellectual property.